Pro-inflammatory Cytokines Drive Deregulation of Potassium Channel Expression in Primary Synovial Fibroblasts - Haidar, Omar; O’Neill, Nathanael; Staunton, Caroline A.; Bavan, Selvan; O’Brien, Fiona; Zouggari, Sarah; Sharif, Umar; Mobasheri, Ali; Kumagai, Kosuke; Barrett-Jolley, Richard (Frontiers in Physiology, 2020)
The synovium secretes synovial fluid, but is also richly innervated with nociceptors and acts as a gateway between avascular joint tissues and the circulatory system. Resident fibroblast-like synoviocytes’ (FLS) calcium-activated potassium channels (KCa) change in activity in arthritis models and this correlates with FLS activation. Objective: To investigate this activation in an in vitro model of inflammatory arthritis; 72hr treatment with cytokines TNF and IL1. Methods: FLS cells were isolated from rat synovial membranes. We analysed global changes in FLS mRNA by RNA-sequencing and then focused on FLS ion channels genes and corresponding FLS electrophysiological phenotype, finally modelling data with Ingenuity Pathway Analysis (IPA) and MATLAB. Results: IPA showed significant activation of inflammatory, osteoarthritic and calcium signalling canonical pathways by cytokines, and we identified ~200 channel gene transcripts. The large KCa (BK) channel consists of the pore forming Kcnma1 together with -subunits. Following cytokine treatment, a significant increase in Kcnma1 RNA abundance was detected by qPCR and changes in several ion channels were detected by RNA-sequencing, including a loss of BK channel -subunit expression Kcnmb1/2 and increase in Kcnmb3. In electrophysiological experiments, there was a decrease in over-all current density at 20mV without change in chord conductance at this potential. Conclusion: TNF and IL1 treatment of FLS in vitro recapitulated several common features of inflammatory arthritis at the transcriptomic level, including increase in Kcnma1 and Kcnmb3 gene expression.